Scrutinizing UML Teaching and Learning Modeling Tools - Almasabe, Abdulqader; Ludi, Stephanie; Elfaki, Abdelrahman (Transactions on Engineering and Computing Sciences, 2023)
The purpose of this paper was to identify, synthesize, and analyze the modeling tools, especially those that support UML modeling and interactive learning methods for Software Engineering and Information Systems Design courses. The goals were to guide both professors and students to choose the proper modeling tools to support software engineering courses objectives. The research identified many successful modeling tools that can help students use what is suitable for learning UML modeling and contribute to engaging students in modeling. Moreover, this research used the meta-ethnography method for synthesizing qualitative results in the area of software engineering, especially modeling. Group of modelling tools have been chosen for this paper based on their usages popularity and successfulness in producing high quality design models. The contribution of this paper is highlighting and defining the strengths, weakness, and limitations of each studied tool.